[József Khogler 4]
Home-newsreels 1966 celebration in July procession with flags, speeches, chorus, sport competitions, 1965 Apr.4 military parade, speeches, many people, politicians on the grandstand, 1965 in front of the register office, the wedding guests, rest-house at the Danube, Zoo, 1970 Christmas, family dinner, the train Budapest - Warszawa, on the airport, in the garden of a country-house, new-born baby, girl, family, home-newsreels 1970 about the stages of a house-building, family together on holiday